Pengaruh Stres Kerja, Motivasi dan Kepemimpinan Terhadap Kinerja Pegawai PT. Bank Rakyat Indonesia (Persero) Tbk Unit Lemabang Palembang - Berandi Suaryansyah (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study aims to determine the effect of work stress, motivation and leadership on employee performance at PT. Bank Rakyat Indonesia (Persero) Tbk. Lemabang Palembang Unit. This study has a population of 33 people. In this study, a sample of 33 people was used as the sample for the instrument trial and the sample for the research analysis data. Sampling in this study using Saturated Sampling technique, namely sampling is done as a whole from the total population. From the results of this study, there is an effect of work stress, motivation and leadership on employee performance at PT. Bank Rakyat Indonesia (Persero) Tbk. Lemabang Palembang Unit. With a sig F value of 0.000 <α (0.05). Correlation (R) variable job stress, motivation and leadership on employee performance at PT. Bank Rakyat Indonesia (Persero) Tbk Lemabang Palembang unit of 0.838 means that it shows a very strong and positive correlation (unidirectional). The coefficient of determination (Rsquare) is 0.702 or 70.2%, which means that the performance variable can be explained or there is an influence with the variables of work stress, motivation and leadership. There is an influence of work stress on performance at PT. Bank Rakyat Indonesia (Persero) Tbk. Lemabang Palembang Unit. Shown the sig t value is 0.047 <α (0.05). There is an influence of motivation on performance at PT. Bank Rakyat Indonesia (Persero) Tbk. Lemabang Palembang Unit. Shown the sig t value is 0.024 <α (0.05). There is a leadership influence on employee performance at PT. Bank Rakyat Indonesia (Persero) Tbk. Lemabang Palembang Unit. Shown the sig t value is 0.047 <α (0.05). Efforts to improve Employee Performance of PT. Bank Rakyat Indonesia (Persero) Tbk. Lemabang Palembang Unit can be done through efforts to reduce workload in the office, work that requires being able to make important decisions, listening to ideas from fellow employees and leaders should pay attention to the implementation of daily tasks, namely through efforts being loyal to the agency, the quantity of work results so that each job can be handled.